If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 5 + 9 + -2p = 0 Reorder the terms: 5 + 9 + 3p + -2p = 0 Combine like terms: 5 + 9 = 14 14 + 3p + -2p = 0 Combine like terms: 3p + -2p = 1p 14 + 1p = 0 Solving 14 + 1p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 1p = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 1p = 0 + -14 1p = 0 + -14 Combine like terms: 0 + -14 = -14 1p = -14 Divide each side by '1'. p = -14 Simplifying p = -14
| (6+15x+36y)/9 | | 9x=14x-10 | | X+2/10=4/5+x-8/3 | | 3w-17=14 | | z-7=1-2z | | 12-2m=28 | | x^2+9x+(81/4)=0 | | 4.3x=-8.6 | | 18-45=4(x-2)-3 | | 3(x-4)=2x+6 | | 5y-x/2=8 | | -111=-3z | | 3r-(2r+1)=2 | | x^2-70x+20100=0 | | 10u-3u=14 | | x^2-70x+21300=0 | | -15t=90 | | 18x-14=15x-10 | | x+5=7-x | | P=5h+5w | | Y+-12=-10 | | 8k+7=7k-12+k | | -5/8+x=-7/24 | | Y+12=-10 | | Y+1.05+7.26= | | z-3.76=79.1 | | 8(-2x-4)12=-52 | | 2.4+5(2.4-1)=7 | | 5x+9=8x+12 | | -21+x=-85 | | (-14i)(-8i)=0 | | 68x-2=(50x+4)+15x |